Web-Based Majapahit Eduwisata Application in Mojokerto Regency - Deby Kurniawan Armananda; Uce Indahyanti; Ade Eviyanti (Procedia of Engineering and Life Science, 2022)
Mojokerto has a very abundant local history. The Majapahit Kingdom was a Hindu-Buddhist kingdom that last ruled the archipelago and is considered the largest kingdom in Indonesian history. Mojokerto. Students also often conduct historical studies by learning directly to these historical places. Because it is considered that learning from books is less effective, starting from the pictures that are displayed only in black and white, taking pictures is less attractive so that it affects students in seeing the shape of the site building. With the condition of learning to use books that are less efficient in seeing the shape of the building. Thus, a web-based historical tourism information system is needed by providing 3-dimensional features. Where 3-dimensional images can be used by users to see images become more real than through the media of books. Based on the above background, the researchers are interested in creating an information system with the title "Application of Web-Based Majapahit Edutourism in Mojokerto Regency.